(untitled) (Revista de Ciências Agroveterinárias, 2017)
This work was carried out in São Joaquim, Santa Catarina, Brazil, during the 2009/2010 crop cycle, in order to evaluate the use of Gafsa rock phosphate combined with poultry litter on tuber yield and leaf mineral composition of organically grown potatoes. The experimental design was a completely randomized block with five replications testing four rates of Gafsa rock phosphate (0; 1.333; 2.666 and 4,000 kg ha-1) combined with the single application of 8 t ha-1 of poultry litter. Regardless of rate applied, the tuber production was not affected by rock phosphate fertilization. Even with the maximum rate of Gafsa rock phosphate, tuber yield was similar to the control with just poultry litter, indicating that the rock phosphate solubility was low during a single crop cycle. Except for P and Ca contents, the poultry litter rate of 8 t ha-1 promoted adequate concentrations for the other nutrients evaluated in the leaves. Due the low P content in the leaves, it was inferred that P was the main limiting nutrient for potato tuber yield in our study.